2011
DOI: 10.1002/btpr.559
|View full text |Cite
|
Sign up to set email alerts
|

Improved NADPH supply for xylitol production by engineered Escherichia coli with glycolytic mutations

Abstract: Escherichia coli engineered to uptake xylose while metabolizing glucose was previously shown to produce high levels of xylitol from a mixture of glucose and xylose when expressing NADPH-dependent xylose reductase from Candida boidinii (CbXR) (Cirino et al., Biotechnol Bioeng. 2006;95:1167-1176). We then described the effects of deletions of key metabolic pathways (e.g., Embden-Meyerhof-Parnas and pentose phosphate pathway) and reactions (e.g., transhydrogenase and NADH dehydrogenase) on resting-cell xylitol yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 50 publications
6
73
2
3
Order By: Relevance
“…The altered glycolysis in pfk mutants routed glucose through pentose phosphate pathway and led to higher NADPH dependent biosynthesis in systems sensitive to NADPH availability reported in [49][50][51] and found by our group [52]. Xylitol formation using NADPH-dependent xylose reductase from Candida boidinii was improved in an E. coli pfkA and sthA mutant [51]. Deletion of pgi and sthA also showed increased glucose utilization and lowered acetate formation.…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 54%
See 3 more Smart Citations
“…The altered glycolysis in pfk mutants routed glucose through pentose phosphate pathway and led to higher NADPH dependent biosynthesis in systems sensitive to NADPH availability reported in [49][50][51] and found by our group [52]. Xylitol formation using NADPH-dependent xylose reductase from Candida boidinii was improved in an E. coli pfkA and sthA mutant [51]. Deletion of pgi and sthA also showed increased glucose utilization and lowered acetate formation.…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 54%
“…In an engineered xylitol producing E. coli strain, double deletions of phosphofructokinase pfk and transhydrogenase sthA or phosphoglucose isomerase pgi and sthA genes were made and both combinations showed increased xylitol yield [47]. The NADPH supply in an engineered E. coli strain was improved by overexpression of fructose 1,6-bisphosphatase II glpX or co-expression of glpX and glucose-6-phosphate 1-dehydrogenase zwf [48].…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that these differences in enzyme properties contribute to variation in metabolism in individual mutant strains under certain conditions. Previous studies have shown that deleting pfkA alone improved NADPH-dependent xylitol production from xylose (Chin and Cirino 2011). We are studying the effects of blocking this step entirely by deleting both PFK genes, pfkA and pfkB, and consider that disrupting glycolysis at this point will then force fructose-6-phosphate to undergo the reversible isomerization reaction that proceeds in the direction of glucose 6-phosphate.…”
Section: Introductionmentioning
confidence: 99%